Green brand awareness and customer purchase intention - Mahama Braimah (Management Science Letters)
Green environmental issues have been of topical interest to both researchers and industrialists for some time now. Research on green brands is relatively limited, especially in developing countries, such as Ghana. This study is therefore designed to determine the relationship between customer awareness of green brand issues and their everyday purchase intentions. Using quantitative techniques, the study interviewed 316 people, conveniently selected from various shopping points in Accra. The study found that, the overwhelming majority of respondents though familiar with green issues did not concern themselves with green issues in their everyday purchase decisions. Again, majority of respondents (54%) familiar with environmental issues confirmed they would not switch from their preferred brands to less fancied brands even if the less fancied brands were more environmentally friendly. It was also confirmed in the study that price, brand name and convenience, performed better than customer concerns for green issues, in influencing respondents’ purchase decisions. It would therefore be strategically significance if advocates, policy makers and business leaders reduce the cost of green products to the final consumer, intensive public education campaigns, coupled with strategic brand building efforts to enhance the level of green brand consumption.